PLANT PATHOLOGY At A Glance - Utpal Kumar Bhattacharyya; Utpal Kumar Bhattacharyya (Ludhiana Kalyani, 2004)
This book is a compilation work and embodies a fairly comprehensive treatment of the objective type questions on fundamental facts and aspect of plant pathology
Plant diseases vectors micro-organisms Plant pathology
Keywords: Plant diseases,vectors, micro-organisms